An assessment of an Australasian pathway for the introduction of transanal total mesorectal excision (taTME). (3rd January 2018) - Abbott, S. C.; Stevenson, A. R. L.; Bell, S. W.; Clark, D.; Merrie, A.; Hayes, J.; Ganesh, S.; Heriot, A. G.; Warrier, S. K.
Abstract: Aim: To evaluate the use of a pathway for the introduction of transanal total mesorectal excision (taTME) into Australia and New Zealand. Method: A pathway for surgeons with an appropriate level of specialist training and baseline skill set was initiated amongst colorectal surgeons; it includes an intensive course, a series of proctored cases and ongoing contribution to audit. Data were collected for patients who had taTME, for benign and malignant conditions, undertaken by the initial adopters of the technique. Results: A total of 133 taTME procedures were performed following the introduction of a training pathway in March 2015. The indication was rectal cancer in 84% of cases. There was one technique‐specific visceral injury, which occurred prior to that surgeon completing the pathway. There were no cases of postoperative mortality; morbidity occurred in 27.1%. The distal resection margin was clear in all cases of rectal cancer, and the circumferential resection margin was positive in two cases. An intact or nearly intact total mesorectal excision was obtained in more than 98% of cases. Conclusion: This study demonstrates the safe and controlled introduction of a new surgical technique in a defined surgeon population with the use of a pathway for training. The authors recommend a similar pathway to facilitate the introduction of taTME to colorectal surgical practice.